2017
DOI: 10.1108/jcom-02-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Authentic enterprise, organization-employee relationship, and employee-generated managerial assets

Abstract: Purpose The purpose of this paper is to examine the impacts of perceived authenticity of organizational behaviors and types of organization-employee relationship (i.e. communal and exchange relationship) on intangible assets of organizations generated by employees’ communicative behaviors (ECBs) (e.g. megaphoning, scouting). Design/methodology/approach A web-based survey was conducted with full-time 528 employees working in medium- and large-sized companies in the USA. Findings Results showed that an organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 39 publications
3
64
1
2
Order By: Relevance
“…Kim, 2001; J. Kim & Sung, 2016; Y. Lee & Kim, 2017), the study found that the current measurements not only bolster the idea of a negative association between the two constructs, but also suggest low reliability (e.g., internal consistency between .5 and .8).…”
Section: Literature Reviewsupporting
confidence: 56%
See 3 more Smart Citations
“…Kim, 2001; J. Kim & Sung, 2016; Y. Lee & Kim, 2017), the study found that the current measurements not only bolster the idea of a negative association between the two constructs, but also suggest low reliability (e.g., internal consistency between .5 and .8).…”
Section: Literature Reviewsupporting
confidence: 56%
“…Kim & Sung, 2016), organization–employee relationships (H.-S. Kim, 2007; Y. Lee, 2017; Y. Lee & Kim, 2017), company–customer relationships (Hall, 2006), publics–foreign government relationship (H.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, trust in superiors strengthens members' intrinsic motivation to contribute to the active sharing of knowledge and creative behaviors (Kim, 2015), and the sense of belonging, mutual trust and thanks, and open interactions among colleagues induce the members to devote themselves to the organization (Mai-Stiina et al, 2017). Furthermore, employees' communicative behaviors (ECB) based on trust are management properties that serve strategic functions in terms of the enterprise (Lee & Kim, 2017;Shen and Kim, 2012;Edwards, 2010;Potter, 2010;Molleda & Roberts, 2008;Bishop, 2003), and such results contribute to motivation to build up trust with employees.…”
Section: Motivationmentioning
confidence: 99%